2008
DOI: 10.1007/s10787-008-8027-6
|View full text |Cite
|
Sign up to set email alerts
|

Wine and health: state of proofs and research needs

Abstract: Regular moderate wine consumption is often associated with reduced morbidity and mortality from to a variety of chronic diseases in which inflammation is a root cause. Wine comes in a wide variety of styles that contain quite different ethanol and polyphenol contents. Controversy remains as to whether the alcohol or polyphenols contribute more to the health benefits of regular moderate wine consumption. The variety of wines available to consumers can be expected to affect health differently in accordance with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 76 publications
0
35
1
Order By: Relevance
“…It must be emphasized that the benefits associated with red wine are dependent upon regular and moderate consumption (Walzem 2008). Although general recommendations are one drink (150 mL) daily for women and two drinks (300 mL) daily for men, individual ideals may vary based on age, gender, genetics, body type, and drug/supplement use.…”
Section: Discussionmentioning
confidence: 99%
“…It must be emphasized that the benefits associated with red wine are dependent upon regular and moderate consumption (Walzem 2008). Although general recommendations are one drink (150 mL) daily for women and two drinks (300 mL) daily for men, individual ideals may vary based on age, gender, genetics, body type, and drug/supplement use.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory markers (such as C-reactive protein and IL-6) have been found to decrease after moderate wine consumption, with superior effects shown for red wine [135]. However, not all studies have found that consumption of wine is associated with a decrease in inflammatory markers [136].…”
Section: Vascular Effectsmentioning
confidence: 99%
“…It has been suggested that 'the beneficial effects of red wine should be attributed to the combined effects of several phenolics rather than individual compounds, and an astute pattern of consumption -i.e. regular moderate rather than binge drinking' [32]. Indeed, several studies have shown synergistic beneficial effects (for example, increased antioxidant activity) when wine phenolics are combined [33].…”
Section: The Resveratrol Controversymentioning
confidence: 99%